An analysis of the causes of, and substandard care associated with, maternal deaths in the Lowland districts of Lesotho 1994-1998 - Ateka, Givans K (Department of Paediatrics and Child Health, 2023)
Lesotho, like many other developing countries, has a high incidence of maternal deaths. Minimal research has however been undertaken to establish the actual maternal mortality rate. The result has been a very wide gap between the officially quoted figure (282/100,000 live births) and the various estimates that have been made over the years. It was only in 1997 that a survey based on active case finding revealed a maternal mortality rate of738/100,000 live births. The researchers noted that not all cases of maternal deaths that occurred during the survey period might have been traced. The figure was however an eye opener to the magnitude of the problem in Lesotho. One of the main limitations of the 1997 survey was that no attempt was made to establish the causes of the documented maternal deaths. This was the motivation behind the current research.